Goal Orientations, Learning Outcomes, and Interest in English and Mathematics Of Grade 9 Students - Pimentel, Khristian Ross P.; Oyzon, Maria Vanessa L. (Alipato, A Journal of Basic Education; Vol 9 (2018), 2018)
This explanatory mixed methods study investigated which achievement goal drives students’ learning processes and outcomes as well as the relationship between students’ goal orientations and learning outcomes, between their goal orientations and interest, and between their learning outcomes and interest in English and Mathematics. The participants in this study were 398 Grade 9 students from four secondary schools in Antipolo City. The findings of the research indicate that students are driven more by mastery goals. No significant difference is found between students’ goal orientations in English and Mathematics and between goal orientations of students from public and private schools. Mastery goals are significantly related with students’ learning outcomes and interest while learning outcomes are significantly related with interest. Several internal and contextual factors that influence students’ goal orientations, learning outcomes, and interest were identified. The results in this study may encourage readers develop latest instructional interventions and innovations, design projects, and reform the curricula in consideration of goal orientation and motivation. Instilling among the students the intrinsic value of learning in any subject is recommended. Keywords: English, goal orientations, interest, learning outcomes, Mathematics, motivation, type of school